2019
DOI: 10.1080/15569527.2018.1517124
|View full text |Cite
|
Sign up to set email alerts
|

Thiol/disulfide homeostasis as a marker of oxidative stress in rosacea: a controlled spectrophotometric study

Abstract: In rosacea patients, the thiol/disulfide balance was observed to shift towards disulfides, which could be considered an indicator of oxidative stress in rosacea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 29 publications
3
33
0
2
Order By: Relevance
“…40,41 The observation that NaF depleted total thiol level further implies oxidative stress and impairment of the normal physiology of the flies since a decrease in the level of thiols has been noted in various medical disorders. 42 In the co-exposure paradigm, resveratrol caused a complete restoration of total thiol level depicting its antioxidative property. This is in accordance with Abolaji et al .…”
Section: Discussionmentioning
confidence: 99%
“…40,41 The observation that NaF depleted total thiol level further implies oxidative stress and impairment of the normal physiology of the flies since a decrease in the level of thiols has been noted in various medical disorders. 42 In the co-exposure paradigm, resveratrol caused a complete restoration of total thiol level depicting its antioxidative property. This is in accordance with Abolaji et al .…”
Section: Discussionmentioning
confidence: 99%
“…Natural immune system disorder, chronic inflammatory responses, microorganisms, neurovascular changes, ultraviolet radiation, and other environmental triggers, food and chemicals taken, alone or in combination, may be responsible for rosacea 5,6 . Recent studies have shown the significant role of oxidative stress on rosacea pathophysiology, and oxidative stress has been argued to be associated with vascular changes, inflammation and oxidative tissue damage in rosacea 3,7 …”
Section: Introductionmentioning
confidence: 99%
“…In more than 40% of rosacea subjects, there is a genetic defect in the production of glutathione transferase. Furthermore, in rosacea patients an altered ratio GSSG/GSH, an accurate indicator of the oxidative status of the cell, is significantly higher in comparison with healthy controls 29 . For these reasons, therapeutic strategies with the aim to increase GSH intracellular levels could be, at least theoretically, an interesting tool counter fighting the pathogenetic role of oxidative stress in rosacea.…”
Section: Discussionmentioning
confidence: 99%